Multicentre emergency department study found that paracetamol and ibuprofen were inappropriately used in 83% and 63% of paediatric cases. - Benini, Franca; Castagno, Emanuele; Barbi, Egidio; Congedi, Sabrina; Urbino, Antonio; Biban, Paolo; Calistri, Lucia; Mancusi, Rossella Letizia (Acta Paediatr, 2018)
AIM: The Pain Practice in Italian Paediatric Emergency Departments assessed how appropriately analgesic drugs were being used by Italian clinicians, based on national paediatric pain guidelines. METHODS: This was a retrospective study that involved 17 Italian members of the Pain In Pediatric Emergency Rooms group. It comprised patients up to the age of 14 years who came to hospital emergency departments with pain and were treated with paracetamol, ibuprofen or opioids, such as codeine, tramadol and morphine. RESULTS: We studied 1471 patients who were given 1593 doses of analgesics. The median time to administration of analgesia was 25 minutes. Opioids were used in 13.5% of the children, and usage increased with age and with more severe clinical conditions, such as trauma: 1.6% of children under two years, 5.9% aged 3-10 and 8.0% aged 11-14. Inappropriate doses of paracetamol, ibuprofen and opioids were used in 83%, 63% and 33% of cases, respectively. The patient's age was a critical determinant of the correct analgesic dosage; for every one-year increase in the patient's age, the probability of appropriate prescriptions rose 14.8%. CONCLUSION: The appropriate use of paracetamol and ibuprofen for paediatric pain in Italian emergency departments was very poor, but improved with age.